LANGUAGE MAINTENANCE AMONG JAVANESE LIVING IN BANDUNG - Riansyah putra Puta, - (2011)
This research is entitled Language Maintenance among Javanese Living in Bandung. The aims of this research are to describe the phenomena of how Javanese people in Bandung maintain their language, the effort they make to maintain their language, and reasons why these Javanese maintain their language. This research employed descriptive method. The research involves ten (10) Javanese people who have been staying in Bandung for more than 10 years. The subjects were categorized into two categories; male and female. The data for the research were in the form of language spoken by respondents, language dominantly used by respondents, kinds of effort which make them use particular language, and reasons why the respondents to use that language. The data were gained through questionnaire, tape recording, and interview. The findings show that there were several types of effort that Javanese make to maintain their language. First, they taught Javanese to their children. Then second they used Javanese in several domains, ally in Family Domain. They maintain their mother tongue because they considered Javanese as a heritage and an ancestor's language and also as indigenous speakers, they feel that it is necessary to use Javanese as the primary language in Family Domain. However, considering maintaining indigenous languages is an essential factor in perpetuating the local culture and the national identity, several concerned parties such as government, teachers, and indigenous speakers should take an active step in order to maintain the language.